Monet/Mitchell painting the French landscape - Kelly, Simon 1969-; Mathieu, Marianne; Pagé, Suzanne 1941- (Saint Louis Art Museum, 2023)
"Monet / Mitchell exhibition catalogue is a fresh view of Monet and Mitchell, two of the most experimental painters of the 20th century. French Impressionist Claude Monet (1840-1926) famously drew inspiration from nature around his home in Giverny: from sunlight on the Seine, textured flowers in his garden, weeping willow trees, and water lilies floating below his Japanese bridge. In 1967, American abstract expressionist Joan Mitchell (1925-92) moved to Vétheuil, a village just miles from Monet's estate. There, the French landscape began to emerge in her paintings: the branches of a linden tree, expansive fields, tangles of greenery, and the river and sky. Monet / Mitchell: Painting the French Landscape examines the aesthetic and thematic dialogue between these important artists, the subject of a 2023 exhibition at the Saint Louis Art Museum. Twelve paintings by each artist reveal similarities in their subject matter, composition, vibrant color, and gestural brushwork. Simon Kelly is curator and head of department of modern and contemporary art at the Saint Louis Art Museum"--
Impressum: "This book is published in conjunction with the exhibition "Monet/Mitchell: Painting the French Landscape" to be presented at the Saint Louis art Museum from March 25 to June 25, 2023"
Includes bibliographical references and index
Keywords: Monet, Claude -- 1840-1926; Mitchell, Joan -- 1925-1992; Rezeption; Monet, Claude / 1840-1926 / Exhibitions; Mitchell, Joan / 1925-1992 / Exhibitions; Landscapes in art / Exhibitions; Ausstellungskatalog -- St. Louis Art Museum -- 25.03.2023-25.06.2023 -- Saint Louis, Mo.; Aufsatzsammlung